PENGARUH MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DI THE GREEN FOREST RESORT BANDUNG - Ferdiana, - (2006)
This study aims to obtain a picture of the influence work motivation on employee performance in the Green Forest Resort Bandung. Problem studied in this research is how to motivate employee of The Green Forest Resort Bandung, how the employee's performance of The Green Forest Resort Bandung, and how the influence of motivation on employee performance in the Green Forest Resort Bandung. Research conducted on all employees of The Green Forest Resort Bandung, which amounted to 51 people. Research using survey methods. Data collection techniques by way of documentation and dissemination of the study questionnaire. Instruments used are questionnaires with Likert scale models of data analysis used is regression analysis. Primary data obtained from the results of empirical research through questionnaires to the employees as respondents. While hoarse secondary data obtained from the documentation of which is owned by The Green Forest Resort Bandung. Based on calculations derived linear regression equation for the employee's performance career development is %4; = 14.352+0.780 X. This shows that for a is 14,352 while for b is 0780. Constants can be interpreted performance of 14,352 employees 14,352 worth of work if the motivation is not implemented well, but if implemented the career development of both the employee's performance in the Green Forest Resort Bandung will increase by 0780. If there is an increase implementation of the independent variable for a respondent, then there is also increasing the employee's performance for 0780. These changes indicate an increase due to the coefficient b marked positive. The results of hypothesis testing showed Fhitung results of the 31.7805 whereas Ftabel error rate α = 0.05 and dk reg b / a = 2 and df res = n - 49 for 2 = 3.1866, meaning Fhitung> Ftabel is 31.7805> 3, 1866. Can be concluded that in a positive and significant influence of motivation to work there on the employee's performance in the Green Forest Resort Bandung.